Respuesta :

(2x + 2) = (3x + -52)

Reorder the terms:
(2 + 2x) = (3x + -52)

Remove parenthesis around (2 + 2x)
2 + 2x = (3x + -52)

Reorder the terms:
2 + 2x = (-52 + 3x)

Remove parenthesis around (-52 + 3x)
2 + 2x = -52 + 3x

Solving
2 + 2x = -52 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
2 + 2x + -3x = -52 + 3x + -3x

Combine like terms: 2x + -3x = -1x
2 + -1x = -52 + 3x + -3x

Combine like terms: 3x + -3x = 0
2 + -1x = -52 + 0
2 + -1x = -52

Add '-2' to each side of the equation.
2 + -2 + -1x = -52 + -2

Combine like terms: 2 + -2 = 0
0 + -1x = -52 + -2
-1x = -52 + -2

Combine like terms: -52 + -2 = -54
-1x = -54

Divide each side by '-1'.
x = 54

Simplifying
x = 54